Studies in Analogy - McInerny, Ralph M. (Springer Netherlands, 1968)
I: The “Ratio Communis” of the Analogous Name -- I. Texts which reject a ratio communis -- II. Texts which imply a ratio communis -- III. The analogy of names -- IV. Some analogous names -- VI. Being is not a Genus -- VII. Resolution and Conclusion -- II: Metaphor and Analogy -- I. Cajetan on metaphor -- II. Analogy vs. Metaphor -- III. Ratio Propria non invenitur nisi in uno -- IV. The signification of names -- V. Ratio communis and ratio propria -- VI. Proprie, Communiter, Metaphorice -- VII. Concluding summary -- III: Metaphor and fundamental ontology -- IV: “Analogy” is analogous -- V: Reply to a Critic -- I. Cajetan and Intrinsic and Extrinsic denomination -- II. Professor Beach as exegete -- III. Professor Beach’s confusion of the Logical and Real -- VI: Is the term soul analogous?.